Legal Responsibility for Misuse of Limited Over-The-Counter Drugs Sold by Small Traders - Krisna Eka Ariestya; Yovita Arie Mangesti (Universitas PGRI Madiun, 2024)
This research is useful to know about the legal responsibility for the misuse of limited free drugs sold by small traders, in order to achieve legal responsibility in health services. The type of normative law used in this research as research with the use of statutory approach (statue approach) and conceptual approach (conceptual approach). Based on this study, it can be concluded that the BPOM Regulation Number and Online Food and Permenkes Number 3 of 2021 concerning Changes in the Classification, Restrictions and Categories of Drugs have regulated the mechanism for the Limited Free Distribution of Pharmaceutical Drugs, but have not fully regulated the legal responsibilities of small traders who produce pharmaceutical preparations at retail for 16 years 2022 related to the supervision of the circulation of drugs circulated in Indonesian regions, PP 8 of 2020 by the Ministerial Regulation of the Food and Drug Supervisory Agency regarding supervision. Drugs and food sold online and Decree of the Minister of Health Number 3 of 2021 concerning Changes in Classification, Restrictions and Classes of Drugs have regulated the mechanism for the circulation of restricted over-the-counter drugs, but have not fully regulated the legal responsibility of drugs. Small traders who produce medicines in retail trade. As a complement to the existing regulations, preventive and repressive efforts require holistic arrangements and revitalization of the supervisory guidance system for the circulation of limited over-the-counter drugs in the community. Legal liability should be provided through a special law that contains authorities so that there is legal certainty over the legal liability for misuse of limited over-the-counter drugs sold by small traders.